Die privatisierte Erfüllung staatlicher Aufgaben Verfassungsrechtliche Probleme und Spielräume Dissertation - Elser, Dominik (sui generis Verlag, 2020)
Can privatizations live up to the expectation of reducing the size of the state? Or will the fears be proven true that privatization can push back on democratic principles and the rule of law? This study tackles four question: What requirements does the constitution lay on the execution of the state tasks? In which respects can the execution of state tasks be privatized? Which problems do the constitutional requirements cause for the privatized execution of tasks? Which room for maneuver does the constitutional requirements leave for the privatized execution? This study does not set out to re-invent the legal phenomenon of privatization or to describe it in a novel way. Rather, this study intends to simplify and to categorize. Privatizations are distinguished fundamentally into whether they concern the task-side or the execution-side of state activity. And it applies the constitutions' requirements in a general way, without delving into the specifics of certain tasks with their special dogmatic categories.